Potensi Pura Mengening Desa Saraseda Tampaksiring, Gianyar Sebagai Wisata Spiritual - Ni Wayan Tiyoni; Ni Wayan Sukerti; Ni Made Suriani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aims to identify the potential of Pura Mengening in Saraseda Village, Tampaksiring District, Gianyar Regency as a spiritual tourism destination based on the 4A components. This research is qualitative descriptive research using data collection methods through observation and interviews related to the 4A components. The data were analyzed descriptively, with the research subjects being the Head of Saraseda Village, the Traditional Village Chief of Saraseda, and the managers of the Pura Mengening tourism destination. The research object is the perception or experience of tourists visiting Pura Mengening. The results of the study indicate that Pura Mengening has strong potential as a spiritual tourism destination based on the four main components (4A): attraction, access, amenities, and ancillary services. The attraction includes the natural beauty of the area with cool air, the sanctity of the temple that is still well-preserved, and the spiritual experience felt by tourists after undergoing the melukat ritual. Access is considered good with roads that are easily reachable, although some points still need improvement, and the travel time from Denpasar city is only 1 hour and 30 minutes. Available amenities include supporting facilities such as toilets, changing rooms, parking areas, and signboards. Ancillary services include the active role of the community and tour guides in maintaining the sanctity of the temple while assisting tourists in the melukat procession. In conclusion, Pura Mengening has great potential to be developed as a sustainable spiritual tourism destination that reflects the harmony of Tri Hita Karana, which is the balance of the relationship between humans, nature, and God.